Development of reflective Islamic garden framework from the Quranic perspective - Mohamed Kamil, Safwah (2019)
Islamic garden design is an application of art in the form of spiritual landscape and is often associated with paradise imagery described in the Holy Qur’an. Past researchers have associated the concept of Islamic gardens with the concept of paradise. Paradise imagery is the inspiration of Islamic garden design using symbols and elements that reflect the images of paradise such as water, rivers, shady trees, fruits, rich ornamentations, and other elements of nature. These garden elements are widely used in both the classic and modern architecture of Islamic gardens. The combination of these elements complied with the concept of Islamic architecture that preserves the relationship between Man and God, and Man and the natural environment. The main purpose of an Islamic garden is thus, to evoke the constant remembrance of the Creator. Preliminary observations reveal the current Islamic gardens in Malaysia only project a superficial aspect of the Islamic garden concept. These are limited to the physical and functional while neglecting the spiritual side of the Islamic garden concept. Thus, this study attempts to investigate the importance of the spiritual value of Islamic garden design. Currently, there is no clear and comprehensive guidelines of Islamic garden design based on the concept of paradise imagery that suits the Malaysian context. There is also a lack of definitions on the concept of Islamic garden design associated with spiritual reflection. This is despite its wide uses in the field of landscape architecture. This study investigates features of the paradise imageries in the Holy Qur’an that can be appropriately translated into the spiritual aspect of Malaysian Islamic garden concept. The study is guided by three research questions. These are what are the concepts of a spirituality for creating reflective Islamic garden, what are the characteristics and elements of paradise imagery according to the Qur’an that are appropriate to be translated into Islamic garden design, and how to develop a framework of a reflective Islamic garden design. The study employed a case study research. It is carried out through archival analyses of the Tafsir Ibn Kathir by Ibn Kathir and the Fizilalil Qur’an by Sayyid Qutb, focus group discussions with relevant experts in the field, and semi-structured interviews with professionals. The data derived from transcripts of interviews were analyzed through constant comparative method. Field notes and documents were used to triangulate the data. The findings of this study will support the theory of Islamic art. The concept of Islamic garden and the concept of paradise imagery provide the foundation for understanding existing Islamic gardens. This theory also emphasizes the Qur’an as the main source of Islamic spirituality. In terms of practical implications, this study will aid landscape architects, academics, scientists and other professionals to gain a better understanding of the features of reflective gardens based on Islamic perspective. The findings will also provide a comprehensive framework for the development of future reflective Islamic gardens.